Titanate Nanotubes-Based Heterogeneous Catalyst for Efficient Production of Biomass Derived Chemicals - Zhou, Shuolin; Wu, Lu; Bai, Junzhuo; Liu, Xianxiang; Lei, Min; Long, Min; Huang, Keying (Frontiers in Chemistry, 2022)
The development of efficient heterogeneous catalytic system to convert plentiful biomass to renewable bio-chemicals is urgent need. Titanate nanotubes-based materials obtained from hydrothermal treatment have been reported as low-cost and efficient catalytic materials in chemical syntheses for bio-based chemicals production with interesting catalytic performance. This mini-review expressly revealed the significance and potential of using titanate nanotubes based material as sustainable and environmentally benign solid catalysts/supports for synthesis of various bio-based chemicals, including glycerol-derived solketal, jet fuel range alkanes precursors, biomass-derived esters, aldehydes, aromatic compounds and so on. From the current knowledge on titanate nanotubes-based material via hydrothermal method here summarized, the future lines of research in the field of catalysis/supports for bio-based chemicals production are outlined.